Automated quantitation of circulating neutrophil and eosinophil activation in asthmatic patients. Issue 6 (1st June 2000) - Leckie, Margaret J; Bryan, Shannon A; Khan, Jamey; Dewar, Ann; Aikman, Sarah L; McGrath, Jennifer; Okrongly, David A; Burman, John F; Barnes, Peter J; Hansel, Trevor T
Abstract : BACKGROUND: Asthma has been associated with eosinophil activation, measured in serum, sputum, bronchoalveolar lavage (BAL) fluid, and urine. A whole blood automated method was developed to assess eosinophil and neutrophil activity in terms of peroxidase content and cell morphology using the Bayer haematology analyser. The method was applied to an in vitro stimulation model when fMLP was added to whole blood and the samples were then analysed for changes in granularity and shape. In addition, cells stimulated with interleukin (IL)-8 were examined by electron microscopy. METHODS: A cross sectional analysis was performed on venous blood from non-atopic, non-asthmatic normal subjects (n = 37), mild (n = 46) and symptomatic (n = 22) asthmatic patients on inhaled β2 agonist only, and more severe asthmatic patients (n = 17) on inhaled and oral corticosteroid therapy. Samples were analysed by the haematology analyser and peroxidase leucograms gated using the WinMDI software program. RESULTS: There were significant differences in the amount of light scatter by the neutrophil populations in the symptomatic (p = 0.007) and severe asthmatic (p = 0.0001) groups compared with the control group. However, abnormalities in eosinophil populations were not observed. In vitro activation of whole blood with fMLP caused similar changes in neutrophil light scatter, suggesting that neutrophil activation is present in peripheral blood of symptomatic asthmatic patients. IL-8 caused a change in shape of the neutrophils seen using transmission electron microscopy. CONCLUSIONS: Evidence of neutrophil activation can be seen in whole blood from patients with asthma using a novel automated method. This may potentially be applied to other inflammatory diseases.